Nanomaterials for electrochemical energy storage devices - Roy, Poulomo; Srivastava, S. K. (Scrivener Publishing ; Wiley, 2020)
Energy storage devices are considered to be an important field of interest for researchers worldwide. Batteries and supercapacitors are therefore extensively studied and progressively evolving. The book not only emphasizes the fundamental theories, electrochemical mechanism and its computational view point, but also discusses recent developments in electrode designing based on nanomaterials, separators, fabrication of advanced devices and their performances.